Films That Work Harder The Circulation of Industrial Film - Hediger, Vinzenz; Hoof, Florian; Zimmermann, Yvonne; Anthony, Scott (Film Culture in Transition, 2024)
Industrial film, non-theatrical film, film studies and science and technology studies, economic history, visual culture